IR Photodecomposition of CH3COCF3. Issue 2 (1988) - Fantoni, R.; Borsella, E.; Piccirillo, S.; Giardini-Guidoni, A.; Teghil, R.
Abstract : IR multiple-photon decomposition of 1, 1, 1-trifluoroacetone has been achieved in bulk by irradiating molecules with 970.55 cm −1 laser radiation. In collisional regime the onset of laser induced breakdown has been observed. Primary fragmentation and subsequent ion and radical secondary reactions have been monitored detecting the spontaneous luminescence with a gateable Optical Multichannel Analyzer.